Pemanfaatan Eco Enzyme dari Bahan Sayuran dan Buah Buahan sebagai Bahan Pupuk Organik (Jurnal Teknologi Pangan dan Ilmu Pertanian, 2024)
Eco enzyme is an organic waste liquid product produced from the fermentation process. Eco enzyme's functions include cleaning vegetables and fruit, cleaning floors, repelling insects and being able to fertilize plants. Eco enzyme has benefits for cleaning because of the acetic acid and alcohol contained in the liquid. The aim of this research is to find out the process of making Eco Enzyme and to find out the benefits of Eco Enzyme organic fertilizer, to find out the results of the nutrient content of the eco enzyme product. This research method is data collection techniques. The data source in this research is a secondary data source, in the form of documentation in the form of photos and videos in the process of making eco enzyme.